2013
DOI: 10.7763/ijeeee.2013.v3.185
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Human Resource Practice: A Synthesized Framework and Causal Model of Leader-Member Exchange, Organizational Justice, Job Satisfaction, and Organizational Citizenship Behavior

Abstract: Research objectives were to determine a synthesized framework and to develop a causal model of leader-member exchange, organizational justice, job satisfaction, and organizational citizenship behavior of textile mill employees in Thailand. The study reported the responses of 619 operational employees from 77 textile mills operating in different parts of Thailand. Data were collected and analyzed with descriptive statistics using SPSS (version 11.5) and assessed with confirmatory factor analysis to confirm the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 50 publications
1
6
0
4
Order By: Relevance
“…The increment in the percentage of variance being explained by LMX and job satisfaction to 42.8% further reaffirmed that when employees with high satisfaction were always thankful to the organization and were likely to produce positive behaviors such as OCB as a gesture of "pay back" the organization. This finding was also congruent with that in non-Western context based on the findings by Kasemsap (2013) in textile factories operating in Thailand, Songbo et al (2013) and Cheung and Wu (2013) in Chinese firms which these researches found the positive mediating effect of job satisfaction in improving employees work outcomes.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The increment in the percentage of variance being explained by LMX and job satisfaction to 42.8% further reaffirmed that when employees with high satisfaction were always thankful to the organization and were likely to produce positive behaviors such as OCB as a gesture of "pay back" the organization. This finding was also congruent with that in non-Western context based on the findings by Kasemsap (2013) in textile factories operating in Thailand, Songbo et al (2013) and Cheung and Wu (2013) in Chinese firms which these researches found the positive mediating effect of job satisfaction in improving employees work outcomes.…”
Section: Discussionsupporting
confidence: 80%
“…Another recent study by Bo-Kai (2013) on the mediating effect of job satisfaction in the relationship between LMX and OCB in 44 elementary schools in Taiwan found that job satisfaction has a partial mediating effect between respect dimension of LMX and OCB towards the organization. Kasemsap (2013) found that job www.ccsenet.org/ass Asian Social Science Vol. 9, No.…”
Section: Job Satisfaction As the Mediatormentioning
confidence: 99%
“…Diğer yandan; Eşitlik, Bekleyiş ve İhtiyaç temelli kuramlara göre, iş doyumu yüksek olan bireyin iş motivasyonu ve iş performansının da yüksek olabileceği ve bunun rol ötesi davranış olan örgütsel vatandaşlık davranışını yükselteceği ifade edilebilir. Yine yazında yapılan çalışmalar bu sonucu desteklemektedir (Kasemsap, 2013;Yılmaz, 2012;Chang, Chen & Yl, 2008 (1998). Resilient adolescents whose parents have serious affective and other psychiatric disorders: Importance of selfunderstanding and relationships.…”
Section: Discussionunclassified
“…Örgütte alınan kararların sonuçlarında ya da süreçlerinde çalışanlar eşit karşılık aldığını düşünürse örgütsel adalet algısı yükselecektir. Eğer çalışanlar herhamgi bir şekilde karşılık alınmadığını düşünürler ise adalet alıgları düşecektir (Greenberg, 1990 Erdoğan, 2002;Scandura ve Tejeda, 2003;Kang, 2004;Erdoğan ve Liden, 2006;Lau, 2008;Ishak ve Alam, 2009;Katrinli vd., 2010;Kasemsap, 2013;Al-Shammari ve Ebrahim, 2015;Turgut vd., 2015). Lee (2001) 2006…”
Section: Lider-üye Etkileşimi öRgütsel Adalet İlişkisiunclassified